Cruise shipping and urban development: State of the art of the industry and cruise ports - Thanos Pallis (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2015)
Cruise shipping has first established as the transportation of pleasure-seeking upper class travellers on seagoing vessels offering one or more ports of call in the United States and the Caribbean. Today this is a highly efficient global business. Modern specialised ships - radically different from cargo vessels - the use of an increasing number of cruise ports of call and turnaround ports so as to provide their customers excellent in-port and destination experiences, and convenient departures from proximal embarkation cities being fundamental tenets of the industry.
Keywords: 330; Kreuzfahrt; Hafenwirtschaft; Stadtentwicklung; Welt